Feed intake, digestibility and growth performance of goats offered napier grass supplemented with molasses protected palm kernel cake and soya waste - Abdullah, Ramli; Akashi, R.; Rahman, M.M.; Nakagawa, T.; Wan Khadijah, W.W. (2013)
The high costs of commercial concentrates limit livestock production in South-east Asia. The efficient use of local feed resources may minimize the costs and improve the productivity. Palm Kernel Cake (PKC) contains moderate levels of protein and energy, which is considered sufficient to meet the requirements of most ruminants. However, its protein degradability in the rumen is high resulting in losing its function as protein source for ruminant. This experiment was aimed to investigate the effect of feeding molasses protected PKC and soya waste on intake, nutrient digestibility and growth performance of young female goats. Eight goats were divided into 2 groups and allocated to respective feeding treatments. The treatments were Tl = napier grass (Pennisetum purpureum)+1.0% commercial pellet of live weight (LW) and T2 = napier grass+1.0% PKC of LW+100 g molasses+55 g soya waste. The results indicated that the Tl treatment increased (p<0.05) napier grass Dry matter (DM) intake (370 vs. 295 g day-1) compared to T2 treatment but the total intakes of DM (584 vs. 668 g day1), organic matter (OM) (532 vs. 585 g day1), Neutral Detergent Fibre (NDF) (308 vs. 344 g day1) and crude protein (CP) (59.2 vs. 58.9 g day1) were similar (p>0.05) for both treatments, respectively. The Tl treatment also increased (p<0.05) apparent digestibility of DM (64.1 vs. 56.3%), OM (67.3 vs. 58.9%), NDF (55.9 vs. 45.2%) and CP (68.4 vs. 52.1%) compared to T2 treatment, but they had no effect (p>0.05) on average daily gain (59.0 vs. 72.1 g day-1) and feed conversion ratio (10.4 vs. 9.6), respectively. It is concluded that supplementing a napier grass-based diet with molasses protected PKC and soya waste can be used as source of protein and energy, exploiting the use of local feed resources for goat production. © 2013 Academic Journals Inc.